Prevalence of Anaemia among the Elderly in Malaysia and Its Associated Factors: Does Ethnicity Matter? - Yusof, Muslimah; Awaluddin, S. Maria; Omar, Maisarah; Ahmad, Noor Ani; Abdul Aziz, Fazly Azry; Jamaluddin, Rasidah; Aris, Tahir; Tan, Maw Pin (Hindawi Publishing Corporation, 2018)
Introduction. Anaemia is common among the elderly, yet it remains an underresearched clinical condition. This study investigates ethnic differences in prevalence of anaemia and identifies potential factors associated with anaemia in the elderly. Methods. Data from the National Health & Morbidity Survey (NHMS) 2015 conducted by Ministry of Health was analyzed. Haemoglobin levels were measured using point-of-care testing, HemoCue® Hb 201+ System ©, from consenting individuals. Demographic information and other clinical information were obtained through a structured questionnaire. Descriptive and multivariate analyses were conducted and significant results were presented as adjusted odds ratio. Results. A total of 3794 participants aged 60 years and older responded to the anaemia module with a response rate of 93.7%. 64.0% of respondents were of Malay ethnicity, 21.6% were Chinese, 6.1% were Indians, and 8.3% were of other ethnicities. The overall prevalence of anaemia among older people was 35.3%. The highest prevalence of anaemia was found among respondents of Indian ethnicity (45.5%). The Indian (aOR: 1.72; 95% CI 1.26-2.34) and Malay (aOR: 1.25; 95% CI 1.04-1.49) ethnic groups were more likely to be anaemic in comparison to those of Chinese ethnicity. Anaemia in older people was also associated with increasing age, history of hospital admission, and the presence of diabetes mellitus. Conclusion. Anaemia in the elderly is associated with Indian and Malay ethnicities, increasing age, hospitalization, and diabetes. Our study has identified important information on a common condition which will guide and assist future studies in reducing the burden of anaemia.